Widespread vertical transmission of secretory immunoglobulin A coated trace bacterial variants from the mother to infant gut through breastfeeding. Issue 22 (19th October 2022) - Qi, Ce; Tu, Huayu; Zhou, Jingbo; Tu, Rundan; Chang, Hong; Chen, Jie; Hu, Haiting; Yu, Renqiang; Sun, Jin
Abstract : Gut microbiota transmission from mother to offspring is critical to infant gut microbiota and immune development. Abstract : Gut microbiota transmission from mother to offspring is critical to infant gut microbiota and immune development. Mother's intestine and breast milk are rich in secretory immunoglobulin A (sIgA), which can coat a specific bacterial spectrum and may be related to bacterial transmission and colonization. Here we analyzed the microbiota and sIgA-coated bacteria of maternal fecal samples and breast milk and infant fecal samples from 19 dyads by 16S rRNA amplicon sequencing. For the sIgA-coated microbiota, both the phylogenetic diversity and the Shannon index of maternal fecal samples show a lower trend than those of infant fecal samples ( P < 0.05). For beta diversity, all three samples were significantly different from each other ( P < 0.05, based on permutational multivariate analysis of variance). We found that sIgA mediated a wide range of vertical transmission of trace bacteria with a relative abundance of amplicon sequence variants of more than 0.0001%. FEAST-based analysis reveals that there was an equal contribution of the maternal gut (median [IQR]; 8.75% [0.90, 62.14]) and breast milk (9.23% [1.69, 22.29]) to infant intestinal total microbiota. The 39 percent of sIgA-coated microbiota in breast milk samples provided as much as 28.49–93.84 percent of all sIgA-coated microbiota in the newborn gut. Therefore, maternal gut and breast milk sIgA-coated bacteria are essential sources of intestinal bacteria in infants. There was high individual variation in the contribution of the maternal gut and breast milk microbiota to the paired infant gut microbiota. Analysis based on the weighted transfer ratio (WTR) explained that diverse sIgA-coated bacteria are transferred from breast milk to the gut of the respective infant, mainly lactic acid bacteria, especially Lactobacillus gasseri (WTR = 2475.5), Enterococcus faecium (WTR = 2438) and Streptococcus salivarius (WTR = 117.71). Bifidobacterium longum, with a WTR of 69.35, is the key sIgA-coated bacteria that are transferred from the mother's gut to breast milk. In conclusion, sIgA mediates the vertical transmission of specific bacteria, to realize the controllable inheritance of the intestinal bacteria and function from the mother to the offspring. This provides a new basis for the screening of probiotics for infant formula addition.